Formation of conductive MOF@Metal oxide micro-nano composites via facile self-assembly for high-performance supercapacitors. (December 2022) - Duan, H.; Lu, J.; Li, S.; Zhang, Y.; Hu, W.; Zhu, R.; Pang, H.
Abstract: Metal-organic frameworks (MOFs), which are promising electrode materials, have been explored for clean energy applications such as electrochemical energy storage. In this study, to enhance the electrical conductivity without decreasing ion transfer efficiency and to balance both activity and stability, we used metal oxides that can directly react with organic ligands and consequently produce their micro-nanocrystallized composites. Furthermore, we investigated the growth process by adjusting the reaction time and by determining the relationship between facet exposure and reaction time. Subsequently, we tested their electrochemical performance and demonstrated that specific facet exposure and small size are critical for achieving high capacitance. This reveals not only the influence of the reaction time on the morphology of conductive MOF composites and size but also the influence of morphology and size on the electrochemical performance. Graphical abstract: A micro-nanocrystallized composite with short electron and ion transfer routes was self-assembled via HHTP directly reacting with MnO2 . By testing their electrochemical performance, we demonstrated that specific facet exposure and small size are critical for achieving high capacitance. Image 1 Highlights: A highly ordered composite of conductive MOF and metal oxide with micro-nanocrystallized structure was fabricated via self-assembly. The micro-nanocrystallization of conductive MOF improved the mass transfer efficiency of these composites. No additional metal salts were required so as to get a convenient and environmentally friendly synthesis. Owing to the synergetic effect, the composite in an aqueous asymmetric supercapacitor exhibited excellent energy storage performance.